ANALISIS SENYAWA ANTIFUNGAL BAKTERI ENDOFIT ASAL TANAMAN JAGUNG (Zea mays L.) - Andini Hanif; Rini Susanti (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2017)
Endophytic bacteria repoted can produce metabolite as antifungal compound. This study was aimed to knowing and obtain antifungal compound wich are produced of endophytic bacteria to control fungal pathogen. Isolation of endophytic bacteria was done using surface sterilization method, furthermore hypersensitive reaction test of bacteria was done for selection pathogenicity of bacteria. Endophytic bacteria was tested their antagonism against fungal pathogen for selection the potential of endophytic bacteria. Isolate of endophytic bacteria which have highest growth inhibitor would be extracted and analyzed the antifungal compound. The result showed that threeisolate of endophytic bacteria wich one potentially in inhibiting fungal pathogen are isolate EF14III, ER1I and ER101. Isolate bacteria ER1I was the most effective in inhibiting the growth of fungal pathogen. Antifungal compound in isolate bacteria ER1I are fenol, lauric acid, propenoic acid, and cyclohexanone.Keywords: Antifungal compound, Endophytic Bacteria, Fungal pathogen